2020
DOI: 10.1016/j.curtheres.2020.100609
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis precipitated by Coronavirus disease 2019 infection: Case series

Abstract: Background Coronavirus has evolved into a devastating pandemic since December 2019. Saudi Arabia's first case was reported in March 2020. Subsequently, some 220,000 cases and 2,000 deaths were recorded through July 2020. COVID-19 infection aggravates glycemic control and provokes acute hyperglycemic crises, according to some reports. We made the same observations in some of our patients diagnosed with COVID-19. However, we are unaware of any reported cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 14 publications
2
25
1
2
Order By: Relevance
“…Furthermore, obesity, hypertension, diabetic nephropathy, and cardiovascular disorders as common comorbidities of diabetes are connected to adverse outcomes of COVID-19 3 . Conversely, new-onset hyperglycemia, ketoacidosis, diabetes, and severe metabolic complications of pre-existing diabetes have been observed in patients suffering from COVID-19 5 11 . Besides single reports of COVID-19 potentially causing or triggering new-onset diabetes 8 , 10 , this phenomenon is currently analyzed in a newly established systematic registry ( http://covidiab.e-dendrite.com/ ) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, obesity, hypertension, diabetic nephropathy, and cardiovascular disorders as common comorbidities of diabetes are connected to adverse outcomes of COVID-19 3 . Conversely, new-onset hyperglycemia, ketoacidosis, diabetes, and severe metabolic complications of pre-existing diabetes have been observed in patients suffering from COVID-19 5 11 . Besides single reports of COVID-19 potentially causing or triggering new-onset diabetes 8 , 10 , this phenomenon is currently analyzed in a newly established systematic registry ( http://covidiab.e-dendrite.com/ ) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…There remains uncertainty surrounding the clinical presentation and management of DKA in those with COVID-19. Case series have demonstrated that COVID-19 can precipitate DKA in those with pre-existing and undiagnosed diabetes (11,12,13). It is clear larger-scale studies are needed to improve insight into the clinical characteristics and relationship between COVID-19 and DKA.…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes COVID-19 pneumonia as well as extrapulmonary complication. There are a few cases of precipitation of new-onset diabetes and diabetes ketoacidosis associated with COVID-19 [3,4]. We present a case of a 44-year-old patient with COVID-19 and concomitant new onset of diabetes and severe diabetes ketoacidosis.…”
Section: Introductionmentioning
confidence: 94%